Evolution of action competence in promoting environmental sustainability in high school students of Cruz das almas – BA (Research, Society and Development, 2019)
Environmental Education should be implemented in a school context using efficient strategies, especially in terms of enhancing students' participation and empowerment in terms of competence for action, as this is the only way to achieve internalization of sustainable habits. In this research, the IVAM methodology was applied to characterize how the competence for the action of high school students in the promotion of water sustainability and, in general, in the sustainable environmental action, developing a project oriented towards sustainable environmental action. An initial and final questionnaires were applied, with mixed treatment of the data, in order to understand the improvement of the students in terms of knowledge and sustainable environmental action. Overall, students improved their action skills, ultimately 92% being more empowered, and their perceptions of the environment became more adjusted to the globalizing conception (30%). Students became better able to solve problems, reflected in the drop in students who, in the end, did not opine on this issue (from 30 to 6%). Thus we conclude that projects oriented towards sustainable environmental action greatly contribute to promoting competence for action in the student.